Examining The Effects Of Green Advertising And Eco-Friendly Packaging On Green Purchase Intention For Sustainable Smes Products In Kerinci Regency - Anggil Nopra Lova; Indra Budaya; Vivi Herlina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The drastic decline in SMEs units in Kerinci Regency from 12,400 to 7,468 within a single year signals a structural crisis requiring immediate evidence-based interventions. This study examines the effects of green advertising and eco-friendly packaging on green purchase intention for sustainable SME products in Kerinci Regency. Using an explanatory quantitative design with 130 respondents selected through purposive sampling, data were analyzed using multiple linear regression. The results reveal that green advertising and eco-friendly packaging each have a positive and significant partial effect on green purchase intention. Simultaneously, both variables significantly influence green purchase intention, though they explain only a limited portion of the variation. Notably, eco-friendly packaging demonstrates a stronger influence compared to green advertising, indicating that Kerinci consumers respond more to tangible physical evidence than abstract persuasive messages. These findings provide practical guidance for SMEs and policymakers in allocating limited resources toward green marketing strategies, emphasizing the prioritization of innovative and informative eco-friendly packaging development to enhance consumer purchase intentions. This research contributes to the green marketing literature by contextualizing consumer behavior theory within rural SME ecosystems undergoing structural pressure and economic contraction.